Improvement of Pit-and-Fissure Sealant Bonding to Enamel with Subpressure Treatment. (28th March 2019) - Zhang, Chang; Li, Yongmei; Zhang, Zutai; Tian, Yueming; Ding, Ning; Ma, Yongping
Abstract : This research evaluated the effects of subpressure on the shear bond strength (SBS) of 80 specimens with flat enamel surfaces and on AgNO3 microleakage of 40 specimens with flat enamel surfaces and 40 specimens with 1 mm deep cavities before and after thermocycling. The enamel of 168 specimens was grounded to a flat surface. Two types of sealants (E and H) were selected. Sealants were applied to enamel surface (88 specimens, group F) either subjected or not to subpressure. The bonding interfaces were observed using scanning electron microscopy (SEM) and the SBS was examined using a universal testing machine before and after thermocycling. The failure mode was also analyzed. For the microleakage test, 80 specimens were grouped as group A (original enamel flat surface) and group B (a round cavity of 1 mm in depth) (40 per group). Sealants were applied to the teeth either subjected or not to subpressure. The specimens were submitted to a microleakage protocol with AgNO3 and analyzed before and after thermocycling. Statistical analysis was performed for the data. The results showed that subpressure eliminated voids on the interface between the enamel and sealants and significantly enhanced specimens' SBS. Although thermocycling reduced SBS significantly, specimens under subpressure after thermocycling still showed higher SBS than specimens under nonsubpressure before thermocycling. The subpressure groups showed a lower microleakage level compared to nonsubpressure groups, though thermocycling caused deeper silver infiltration. In addition, different sealants showed no significant effect on the SBS and microleakage performance. Overall, subpressure application improves sealant bonding and retention rate and has potential to prevent secondary caries.